Effect of riboflavin deficiency on development of the cerebral cortex in Slc52a3 knockout mice - Jin, Congyun (Sci Rep, 2020)
Riboflavin transporter 3 (RFVT3), encoded by the SLC52A3 gene, is important for riboflavin homeostasis in the small intestine, kidney, and placenta. Our previous study demonstrated that Slc52a3 knockout (Slc52a3−/−) mice exhibited neonatal lethality and metabolic disorder due to riboflavin deficiency. Here, we investigated the influence of Slc52a3 gene disruption on brain development using Slc52a3−/− embryos. Slc52a3−/− mice at postnatal day 0 showed hypoplasia of the brain and reduced thickness of cortical layers. At embryonic day 13.5, the formation of Tuj1(+) neurons and Tbr2(+) intermediate neural progenitors was significantly decreased; no significant difference was observed in the total number and proliferative rate of Pax6(+) radial glia. Importantly, the hypoplastic phenotype was rescued upon riboflavin supplementation. Thus, it can be concluded that RFVT3 contributes to riboflavin homeostasis in embryos and that riboflavin itself is required during embryonic development of the cerebral cortex in mice.